USING LATTICE METHODS TO SOLVE REAL-OPTIONS VALUATION PROBLEMS WITH LEARNING OPTIONS AND CHANGING VOLATILITY - FEBRIANTI (NIM: 20114007) , WERRY
Real options are related to investment in long term. Investment in the long term causes uncertainty in real asset price and management flexibility. Since real options have some similarity with financial options so that some solution methods in financial options especially lattice methods may be used to real options problems. Adding learning options as a feature of real options implies modification of the lattice methods. At the beginning of collecting information, the uncertainty of the project value is commonly high. The uncertainty of the project value is related to the project’s volatility so that when the uncertainty of the project value is high then the project’s volatility is also high. Since there is possibility to collect information through learning options, it will reduce the uncertainty of the project value and so does the project’s volatility. The changing volatility in binomial lattice is constructed by using different length of time steps during investment period, so the higher volatility is, the shorter the length of time steps is. The changing volatility is also modeled in trinomial lattice that contain the learning options. In this case, unlike the standard trinomial lattice, the probability of movement project’s value will not be constant in each period of investment. An application of the above methods to a problem of real options in the field of petroleum engineering is also given.